Interfacing tetrapyridyl-C60 with porphyrin dimers via π-conjugated bridges: artificial photosynthetic systems with ultrafast charge separation. Issue 33 (24th July 2018) - Stangel, Christina; Plass, Fabian; Charisiadis, Asterios; Giannoudis, Emmanouil; Chararalambidis, Georgios; Karikis, Kostas; Rotas, Georgios; Zervaki, Galateia E.; Lathiotakis, Nektarios N.; Tagmatarchis, Nikos; Kahnt, Axel; Coutsolelos, Athanassios G.
Abstract : A novel D–π–A supramolecular hybrid system is reported, consisting of a fullerene derivative as electron acceptor and zinc porphyrin dimers as electron donors. Abstract : We report on the synthesis, characterization and photophysical properties of a donor–bridge–acceptor supramolecular hybrid system, consisting of a tetrapyridyl fullerene derivative (C60 -tpyr ) as electron acceptor, with the four pyridyl groups as part of oligophenyleneethynylene/phenylenevinylene bridges, and zinc porphyrin dimers(ZnP)2 as electron donor species. Based on the metal-to-ligand coordination between the zinc metal centers of(ZnP)2 and the four pyridyl entities ofC60 -tpyr, a strong binding constant (5 × 10 5 M −1 ) for the formation ofC60 -tpyr·[(ZnP)2 ]2 was evidenced. Insights into the electronic interactions between the photoactive(ZnP)2 units andC60 -tpyr emanated from complementary physicochemical assays, which were further supported by theoretical calculations. Notably, the absorption and emission titration assays revealed strong interactions between the electron donor and acceptor species withinC60 -tpyr·[(ZnP)2 ]2, both in the ground and excited state. Moreover, femtosecond and nanosecond laser photolysis transient absorption measurements were performed and provided solid evidence for intramolecular electron transfer processes derived from the singlet excited state of(ZnP)2 toC60 -tpyr . Comparison with systems in which either four monomeric zinc porphyrins (ZnP ) were complexed withC60 -tpyr or a(ZnP)2 was coordinated with a dipyridylfullerene revealed the beneficial role ofC60 -tpyr in increasing the lifetime of charge-separation.